MEWUJUDKAN PENDIDIKAN JIHAD UNTUK MELAWAN TERORIS - Muzamil Muzamil (Turatsuna : Jurnal Keislaman dan Pendidikan, 2019)
Education is one of fields that determine the national personality. The good of the nation can be seen from the implementation of education that affects it. Antiterrorism jihad education is a way of forming and strengthening the thinking patterns and attitudes of students towards the belief development and religious understanding of a person or group of people. Such methods have to be educational activities that continue to be carried out wherever and whenever the potential for radicalism exists and develops. The influence of social environment or the network of local radicalism to global power can be muted or it is possible that it will fail to grow due to the ongoing anti-terrorism jihad education. Keywords: education, jihad, anti-terrorism, society, state  Pendidikan merupakan salah satu bidang yang menentukan kepribadian bangsa. Baik buruknya bangsa dapat dilihat dari penyelenggaraan pendidikan yang mempengaruhinya.  Pendidikan jihad anti terorisme merupakan cara membentuk dan menguatkan pola berfikir dan sikap subyek didik terhadap perkembangan aliran dan pemahaman keagamaan seseorang atau sekelompok orang. Cara demikian haruslah menjadi aktifitas edukatif yang bisa terus dijalankan dimanapun dan kapanpun  potensi radikalisme  ada dan berkembang. Pengaruh dari lingkungan pergaulan atau jaringan kekuatan radikalisme lokal hingga global dapat diredam atau kemunginan akan gagal tumbuh berkembang akibat  berlangsungnya pendidikan jihad anti terorisme. Kata kunci: pendidikan, jihad, anti terorisme, masyarakat, negara